Efektivitas Konseling Kelompok dengan Teknik Appreciative Inquiry Dalam Meningkatkan Filial Piety pada Remaja di SMA Swasta Utama - Aida Sari Haji Nst; Fauzia Nasution (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effectiveness of group counseling with Appreciative Inquiry techniques in improving filial piety (obedience and respect for parents) in adolescents at Utama Private High School. This study uses an experimental quantitative research method. Based on the results of the study, there is a significant difference between the pre-test and post-test results, from the results of the Wilcoxon Signed Ranks Test showing that there is a negative rank value (N = 1), while all data (N = 17) show positive ranks with a mean rank of 9.24 and a total sum of ranks of 157.00. This shows that 17 of the 18 participants experienced an increase in scores from pretest to posttest. The significance value of Asymp. Sig. (2-Tailed) is 0.002 <0.05, which means there is a significant difference between the pretest and posttest. Thus, the author concludes that the Appreciative Inquiry intervention on the quality of students' filial piety is proven effective in increasing the change score from pretest to posttest. This demonstrates that Appreciative Inquiry can improve and change students' attitudes toward filial piety.